How to preserve the visible content of films in visual form throughout the analytical process? - Grunditz, Sofia (Visual Studies, 2021)
This article demonstrates an analytical and arts-based approach using drawings as tools to retain the visual information in a film visual, throughout the research process as well as for thinking. The approach brings in methods and theory from disciplines using visual materials as data: Visual Anthropology, Ethnomethodology/Conversation Analysis (EMCA), Art History and Film Studies. Furthermore, tools and reflections on how to sketch, draw and construct analytical images using paper and pen, technical tools such as features in movie players and image processing software, and basic drawing apps on a tablet, are presented and demonstrated in empirical examples from a study on preschool naptime. The drawn analysis are abstractions of the visual data where certain visual aspects, visible in the film, are re-used thus creating a direct link between the film and the drawing that preserve visual aspects of the original throughout the research process. This gains new knowledge, further and different knowledge than just using words. Also, the drawings address ethical issues as children's right to anonymity in a study. The visual remake is proposed as a term for this arts-based approach to highlight, enhance and visualise the features of films that are of special interest to an enquiry and facilitate comparative analysis.